1992
DOI: 10.1063/1.107779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate temperature on the microstructure of YBa2Cu3O7−δ films grown on (001) Y-ZrO2 substrates

Abstract: High-quality YBa2Cu3O7−δ films grown on (001) single-crystal Y-ZrO2 substrates by pulsed laser deposition have been studied as a function of substrate temperature using transmission electron microscopy. A transition from epitaxial films to c-axis oriented polycrystalline films was observed at 740 °C. An intermediate, polycrystalline, BaZrO3 layer was formed from a reaction between the film and the substrate. A dominant orientation relationship of [001]YBCO//[001]int. layer//[001]YSZ and [110]YBCO//[110]int. la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…1 They influence the motion of domain boundaries in ferroelectrics and disrupt superconductivity in oxide superconductors, causing "weak links" and Josephson junctions. 6,9,[12][13][14] If understood and controllable, these ϳ9 ± boundaries (and 45 ± 2 9 ± 36 ± grain boundaries) would be a significant improvement over 45 ± bi-epitaxy boundaries for many applications because of the higher critical current densities of the Josephson junctions formed at these lower-angle boundaries. One example of grain boundary engineering is the "biepitaxy" process used to introduce 45 ± grain boundaries into epitaxial oxide superconductor films.…”
Section: Introductionmentioning
confidence: 99%
“…1 They influence the motion of domain boundaries in ferroelectrics and disrupt superconductivity in oxide superconductors, causing "weak links" and Josephson junctions. 6,9,[12][13][14] If understood and controllable, these ϳ9 ± boundaries (and 45 ± 2 9 ± 36 ± grain boundaries) would be a significant improvement over 45 ± bi-epitaxy boundaries for many applications because of the higher critical current densities of the Josephson junctions formed at these lower-angle boundaries. One example of grain boundary engineering is the "biepitaxy" process used to introduce 45 ± grain boundaries into epitaxial oxide superconductor films.…”
Section: Introductionmentioning
confidence: 99%
“…However, a special epitaxy with the YBCO u-axis making an angle of about 9" with the substrate [ 1001 was also found [ 61. In our paper these epitaxies are defined as 0", 45') and 9" epitaxy, respectively. Alarco et al [ 7 ] reported that the dominant orientation relationship at low temperatures (650%) was 45" epitaxy while at higher temperatures (750°C) it was 0" epitaxy. Fork et al [ 61 grew homoepitaxial YSZ and heteroepitaxial CeOz on YSZ single-crystal substrates and reported that this procedure dramatically improves the epitaxy of YBCO and reduces the number of low-and high-angle grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] In that system the out-of-plane orientation relationship, (001) YBa 2 Cu 3 O 7 k (001) YSZ, was found to remain constant, while the in-plane orientation relationship was observed to change with growth temperature. 36 Fig.…”
mentioning
confidence: 92%